In Vitro Susceptibility of Colistin Against Multidrug Resistant Klebsiella Pneumoniae Clinical Isolates - Fayyaz, Muhammad; Zafar, Humaira; Mirza, Irfan Ali; Meral, Uzma; Hussain, Aamir; Khalil, Hafsa (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To determine in-vitro efficacy of colistin against resistant Klebsiella Pneumoniae clinical isolates. Study Design: Cross-sectional study.Place and Duration of Study: Microbiology Department of Pathology Lab, Armed Forces Institute of Cardiology & National Institute of Heart Diseases, Rawalpindi, Pakistan, from Jan 2021 to Dec 2021.Methodology: This cross-sectional study was carried out at the microbiology department of pathology lab, Armed Forces institute of Cardiology & National Institute of Heart Diseases, Rawalpindi through Jan 2021 to Dec 2021. Sampling was done by nonprobability consecutive technique. Antimicrobial susceptibility testing was done for all clinical isolates of KP.Results: A total of 3066 culture and sensitivity requests were received, out of these 663(21.6%) specimens revealed growth of different microorganisms. Amongst 663 culture positive isolates, 150(22.6 %) were identified as KP. Antibiotic susceptibility of KP showed >90% isolates resistant to 3rd & 4th generation cephalosporins, cotrimoxazole, ampicillin+salbactum and coamoxiclav. Aminoglycosides, quinolones, meropenem, aztreonam and tazobactum+pipracillin were found resistant in >80% isolates and doxycycline and imipenem in >70% isolates. Resistance to minocycline was 58%, chloramphenicol 40.7% and Tigecycline 38.7%. The least resistance was noted in Colistin 16%.Conclusion: A very high antimicrobial resistance was observed in KP isolates against penicillins, cephalosporins, ampicillin beta lactamase inhibitor combinations, quinolones, aminoglycosides, carbapenems and cotrimoxazole. Comparatively tigecyclines and chloramphenicol were found to be less resistant than other antimicrobials to manage MDR and XDR cases. Colistin has excellent efficacy against MDR and XDR KP isolates.